PENGARUH KONSERVATISME AKUNTANSI, INTENSITAS MODAL, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2014 – 2017) - Mulyani, Novi Tri; Harimurti, Fadjar; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
Tax avoidance is a tax avoidance activity carried out in a legal manner that does not violate applicable laws. This study aims to determine the effect of accounting conservatism, capital intensity, and firm size on tax avoidance. The object of this research is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The sample selection technique uses purposive sampling, in order to obtain 11 samples of companies that meet the criteria. Data used in the form of secondary data originating from the company's financial statements, while the data analysis technique uses multiple linear regression analysis using SPSS 2.1. The results showed that accounting conservatism, capital intensity did not significantly influence tax avoidance, while the size of the company had a significant positive effect on tax avoidance.